Target Properties Effects on Central versus Peripheral Vertical Fusion Interaction Tested on a 3D Platform. (4th March 2017) - Zhang, Di; Neveu, Pascaline; Fattakhova, Yulia; Ferragut, Stéphanie; Lamard, Mathieu; Cochener, Béatrice; de Bougrenet de la Tocnaye, Jean-Louis
ABSTRACT: Purpose : We investigated the impact of target properties on vertical fusion amplitude (VFA) using a 3D display platform; the performance of the subjects allowed us to assess how central and peripheral retina regions interact during the fusion process. Material and Methods : Fourteen subjects were involved in the test. VFA was recorded by varying the viewing distance, target complexity, disparity velocity, lighting condition and background luminance. Base-up prisms were introduced to create vertical disparity in the peripheral retinal area, whereas an offset compensation was added in the central area. Data were analyzed in JMP software using T-test and repeated-measures ANOVA tests. Results : VFA is significantly affected by target properties including viewing distance, target complexity and disparity velocity; the impact from lighting condition and background luminance is not significant. Although central retina plays a crucial role in the fusion process, peripheral regions also affect the fusion performance when stimulus size on retina and contents disparity values are modified between central and peripheral vision. Conclusion : Vertical fusion is affected by various target properties. For the first time, peripheral vertical disparity direction effects on central fusion and eye motion response have been explored. Besides, a quantitative interaction of central and peripheral fusion is observed, which could be applied in clinical measurement on binocular disease concerning central and peripheral vision conflict.